The Influencing Factors on the Effectiveness of Talent Training in China’s Modern Industrial Colleges - Guo, Dan; Lertatthakornkit, Tippawan; Kuayraksa, Yadanant (Journal of Dhamma for Life, 2026)
The purposes of this research were: 1) to study the levels of influencing factors of China’s modern industrial colleges; 2) to study the levels of effectiveness of talent training of China’s modern industrial colleges; and 3) to analyze to the effect of influencing factors on the effectiveness of talent training of China’s modern industrial colleges. This research employed a quantitative research methodology. The samples used in this study consisted of 268 participants working at the selected modern industrial colleges in China. The questionnaire was used the instrument to collect data. The research results showed that: 1) Influencing factors, in total, were perceived at high level (M = 3.71, SD = 0.70). 2) The effectiveness of talent training, in total, was perceived at high level (M = 3.75, SD = 0.72). 3) The results of Multiple Regression Analysis showed that influencing factors had an effect on talent training with statistical significance at the .01 (F=52.37, p=.000). The forecasting equation from multiple regression analysis can predict the effect of influencing factors on talent training at 76 percent (Adjusted R2 = .76), whereas, the rest 24 percent was the result of other factors, which were not taken into account in this study. In particular, student demand matching had the highest effect on talent training (Beta = 0.28, p < .01), followed by teachers’ industry participation (Beta = 0.25, p < .01), depth of school-enterprise cooperation (Beta = 0.23, p < .01), resource integration capability (Beta = 0.21, p < .01) and inter-organizational trust (Beta = 0.18, p < .01).